The electrical, optical properties of AlSb polycrystalline thin films deposited by magnetron co-sputtering without annealing - 黄征 武莉莉 黎兵 郝霞 贺剑雄 冯良桓 李卫 张静全 蔡亚平 (Chinese physics B, 2010)
In order to fabricate A1Sb polycrystalline thin films without post annealing, this paper studies a technology of magnetron co-sputtering onto intentionally heated substrate. It compares the structural characteristics and electrical properties of A1Sb films which are deposited at different substrate temperatures. It finds that the films prepared at a substrate temperature of 450 ℃ exhibit an enhanced grain growth with an average grain size of 21 nm and the lattice constant is 0.61562 nm that goes well with unstained lattice constant （0.61355 nm）. The ln（σdark） -1/T curves show that the conductivity activation energy is about 0.38 eV when the film is deposited at 450 ℃ without an annealing. The transmittance and reflectance spectra show that the film deposited at 450 ℃ has an optical band gap of 1.6 eV. These results indicate that we have prepared A1Sb polycrystalline films which do not need a post annealing.